Strengths test on a glass reinforced thermoplastic (Acrylonitrile Butadiene Styrene (ABS)) / [mikrofilem] - 388906 Syed Azman Shah Syed Noordin
Thesis (BSc Mechanical Engineering) - Brighton Polytechnic, 1981